Visuomotor adaptation in the absence of input from early visual cortex. (June 2019) - Striemer, Christopher L.; Enns, James T.; Whitwell, Robert L.
Abstract: Prism adaptation is a time-honored tool for studying how the motor system adapts to sensory perturbations. Past research on the neural substrates of prism adaptation has implicated the posterior parietal cortex (PPC) and the cerebellum, under the assumption that these structures gain their visual input from the dominant retinogeniculate pathway to V1. Here we question whether this pathway is even required for visuomotor adaptation to occur. To investigate this, we examined prism adaptation in 'MC', someone who is blind to static stimuli following bilateral lesions that encompass much of her occipital cortex and the caudal-most areas of ventrotemporal cortex. Remarkably, MC shows evidence of prism adaptation that is similar to healthy control participants. First, when pointing with either the left or the right hand, MC shows spatial realignment ; the classical after-effect exhibited by most people when adapting to displacing prisms. Second, MC demonstrates strategic recalibration – a reduction in her pointing error over time – that is similar in magnitude to healthy controls. These findings suggest that the geniculostriate pathway is not necessary for visuomotor adaptation to take place. Alternatively, we suggest that an extrageniculostriate pathway which provides visual inputs to the cerebellum from area MT and the PPC via the dorsolateral pons plays a significant and appreciable role in the guidance of unconscious automatic visuomotor adaptation.